High and stable substrate specificities of microorganisms in enhanced biological phosphorus removal plants. (16th January 2013) - Kindaichi, Tomonori; Nierychlo, Marta; Kragelund, Caroline; Nielsen, Jeppe Lund; Nielsen, Per Halkjær
Summary Microbial communities are typically characterized by conditions of nutrient limitation so the availability of the resources is likely a key factor in the niche differentiation across all species and in the regulation of the community structure. In this study we have investigated whether four species exhibit any in situ short‐term changes in substrate uptake pattern when exposed to variations in substrate and growth conditions. Microautoradiography was combined with fluorescence in situ hybridization to investigate in situ cell‐specific substrate uptake profiles of four probe‐defined coexisting species in a wastewater treatment plant with enhanced biological phosphorus removal. These were the filamentous 'Candidatus Microthrix' and Caldilinea (type 0803), the polyphosphate‐accumulating organism 'Candidatus Accumulibacter', and the denitrifying Azoarcus. The experimental conditions mimicked the conditions potentially encountered in the respective environment (starvation, high/low substrate concentration, induction with specific substrates, and single/multiple substrates). The results showed that each probe‐defined species exhibited very distinct and constant substrate uptake profile in time and space, which hardly changed under any of the conditions tested. Such niche partitioning implies that a significant change in substrate composition will be reflected in a changed community structure rather than the substrate uptake response from the different species.